Positive electrode active material, positive electrode comprising same, and lithium secondary battery

By using a bimodal structure of lithium nickel-based transition metal oxide in the positive electrode active material of lithium secondary batteries, the problems of particle fracture and cracking are solved, and high roll pressure density and excellent high temperature performance are achieved.

CN120202559APending Publication Date: 2025-06-24LG ENERGY SOLUTION LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380079373.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-26
Filing Date
2023-12-21
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing lithium nickel cobalt manganese oxide positive electrode active materials are prone to particle rupture and cracking during the manufacturing and charging and discharge process, resulting in increased side reactions with the electrolyte, gas generation and active material deterioration, and reduced life characteristics.

Method used

A bimodal positive electrode active material is used, including large-particle and small-particle size lithium-nickel-based transition metal oxides. Through the specific design of particle size distribution, particle fracture and cracks are reduced and roller pressure density is improved.

Benefits of technology

It significantly reduces particle fractures and cracks, improves roll pressure density, improves energy density, extends high temperature life and storage characteristics, and optimizes output characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005403568320000181
    Figure BDA0005403568320000181
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material comprising a large-particle-size lithium nickel-based transition metal oxide and a small-particle-size lithium nickel-based transition metal oxide, in which the large-particle-size lithium nickel-based transition metal oxide is in the form of secondary particles which are aggregates of primary particles, and the small-particle-size lithium nickel-based transition metal oxide is in the form of a lithium nickel-based transition metal oxide. The small-particle-size lithium nickel-based transition metal oxide is in the form of at least one of a single particle and a quasi-single particle, the single particle is formed by a particle node, and the quasi-single particle is a compound of 30 or less particle nodes. Applying the positive electrode active material to a positive electrode to provide a lithium secondary battery in which cracking of positive electrode active material particles is suppressed, thereby improving lifespan and output characteristics, and reducing the amount of gas generation.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross - reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10 - 2022 - 0184870, filed on December 26, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical field

[0003] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode including the positive electrode active material, and a lithium secondary battery. Background art

[0004] A lithium secondary battery generally consists of a positive electrode, a negative electrode, a separator, and an electrolyte, where the positive electrode and the negative electrode include active materials capable of intercalating and deintercalating lithium ions.

[0005] As positive electrode active materials for lithium secondary batteries, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used. Among them, lithium cobalt oxide has the advantages of high working voltage and excellent capacity characteristics, but the price of cobalt as a raw material is high and its supply is unstable, making it difficult to commercially apply it to large - capacity batteries. The structural stability of lithium nickel oxide is poor, making it difficult to obtain sufficient life characteristics. At the same time, lithium manganese oxide has excellent stability but has a problem of poor capacity characteristics. Therefore, in order to compensate for the problems of lithium transition metal oxides containing only Ni, Co, or Mn, lithium nickel - based transition metal oxides containing two or more transition metals have been developed, and in particular, lithium nickel cobalt manganese composite oxides containing Ni, Co, and Mn are widely used in the field of electric vehicle batteries.

[0006] Conventional lithium nickel cobalt manganese oxides are usually in the form of spherical secondary particles in which dozens to hundreds of primary particles are aggregated. However, for lithium nickel cobalt manganese oxides in the form of secondary particles with a large number of aggregated primary particles, there are problems that particle breakage may occur during the roll - pressing process when manufacturing the positive electrode, causing the primary particles to fall off, and cracks may appear inside the particles during charge and discharge processes. When particle breakage or cracks occur in the positive electrode active material, the contact area with the electrolyte increases, which increases gas generation and active material deterioration caused by side reactions with the electrolyte, thereby reducing the life characteristics. Summary of the invention

[0007] [Technical problem]

[0008] The present invention aims to solve the above problems and provide a positive electrode active material that can improve the energy density by adopting a bimodal positive electrode active material, can suppress particle breakage and cracks during electrode manufacturing and charge / discharge processes, and has excellent rolling density.

[0009] In addition, the present invention provides a positive electrode and a lithium secondary battery that have a low cracking rate by including the above positive electrode active material, and thus reduce side reactions with the electrolyte, resulting in improved high-temperature life and output characteristics and improved high-temperature storage characteristics.

[0010] [Technical Solution]

[0011] To solve the above problems, according to one aspect of the present invention, there is provided a positive electrode active material comprising: large-particle-size lithium nickel-based transition metal oxide and small-particle-size lithium nickel-based transition metal oxide, wherein the large-particle-size lithium nickel-based transition metal oxide is in the form of secondary particles, the secondary particles are aggregates of primary particles, and the small-particle-size lithium nickel-based transition metal oxide is in the form of at least one of single particles and quasi-single particles, the single particle is formed by one nodule, the quasi-single particle is a composite of 30 or fewer nodules, wherein the volume cumulative particle size distribution diagram obtained from the particle size distribution (PSD) of the positive electrode active material includes a peak P on the small-particle-size side S and a peak P on the large-particle-size side L , and wherein the B value obtained by the following Equation 1 is 4.0 to 17.0:

[0012] [Equation 1]

[0013] B = (D max - D L ) / (D S - D min )

[0014] wherein, D max is the maximum particle size of the positive electrode active material, D min is the minimum particle size of the positive electrode active material, D L is the median particle size of peak P L , and D S is the median particle size of peak P S .

[0015] To solve the above problems, according to another aspect of the present invention, there is provided a positive electrode comprising the positive electrode active material of the present invention.

[0016] To solve the above problems, according to still another aspect of the present invention, there is provided a lithium secondary battery including the positive electrode of the present invention.

[0017] [Advantageous Effects]

[0018] The positive electrode active material for a lithium secondary battery according to the present invention includes lithium nickel-based transition metal oxides in the form of single particles and / or quasi-single particles having excellent particle strength, and lithium nickel-based transition metal oxides in the form of secondary particles, which are aggregates of primary particles, thereby reducing the occurrence of particle breakage or cracks caused by roll pressing during the manufacture of an electrode, achieving an excellent roll pressing density level, and improving the energy density due to the bimodal particle size characteristics.

[0019] In addition, in the positive electrode active material for a lithium secondary battery according to the present invention, particle breakage can be minimized, thereby reducing side reactions with the electrolyte and thus reducing the gas generation amount. In addition, during the charge and discharge processes, changes in the crystal structure can be minimized, thereby suppressing deterioration of the positive electrode active material and thus improving the high-temperature life characteristics and high-temperature storage characteristics. In addition, due to the low resistance increase rate, the output characteristics can be excellent. Detailed Description

[0020] The terms or words used in the specification and claims of the present application should not be construed as limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical spirit of the present invention based on the principle that the inventor can fully define the concept of the term to best describe his invention.

[0021] It should be understood that terms such as "comprising", "including", and "having" used herein are intended to indicate the presence of the implemented features, numbers, steps, components, or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0022] In the present disclosure, a "single particle" is a particle formed by a single nodule. In the present disclosure, a "nodule" refers to a particle unit that can be a single crystal without a crystalline grain boundary or a polycrystal without an obvious grain boundary when observed using a scanning electron microscope (SEM) at a magnification of 5000 to 20000 times in the field of view. In the present disclosure, a "quasi-single particle" refers to a particle that is a composite formed by 30 or fewer nodules.

[0023] In the present disclosure, a "secondary particle" refers to a particle formed by the aggregation of dozens to hundreds of primary particles. More specifically, a secondary particle is an aggregate of 50 or more primary particles.

[0024] The term "particle" used in the present disclosure may include any one or all of single particles, quasi-single particles, primary particles, nodules, and secondary particles.

[0025] In the present disclosure, "D 50 " refers to the particle size at 50% in the volume-based particle size distribution of the positive electrode active material powder. The average particle size D50 It can be measured by the laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (for example, Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz with an output of 60 W. Thereafter, the average particle size can be determined by obtaining a volume cumulative particle size distribution diagram and then obtaining the particle size corresponding to 50% of the volume cumulative amount.

[0026] Hereinafter, the present invention will be described in more detail.

[0027] Positive electrode active material

[0028] The positive electrode active material of the present invention includes: large particle size lithium nickel-based transition metal oxide and small particle size lithium nickel-based transition metal oxide, wherein the large particle size lithium nickel-based transition metal oxide is in the form of secondary particles, the secondary particles are aggregates of primary particles, and the small particle size lithium nickel-based transition metal oxide is in the form of at least one of single particles and quasi-single particles, the single particle is formed by one grain segment, the quasi-single particle is a composite of 30 or less grain segments, wherein the volume cumulative particle size distribution diagram obtained from the particle size distribution (PSD) of the positive electrode active material includes a peak P on the small particle size side S and a peak P on the large particle size side L , and wherein the B value obtained by the following Equation 1 is 3.0 to 17.0:

[0029] [Equation 1]

[0030] B = (D max - D L ) / (D S - D min )

[0031] wherein, D max is the maximum particle size of the positive electrode active material, D min is the minimum particle size of the positive electrode active material, D L is the median particle size of peak P L , and D S is the median particle size of peak P S .

[0032] Lithium nickel-based transition metal oxides in single particle and / or quasi-single particle form have higher particle strength compared to lithium nickel-based transition metal oxides in the form of secondary particles with dozens to hundreds of primary particles aggregated conventionally. Therefore, there are fewer particle ruptures during the rolling process. In addition, the lithium nickel-based transition metal oxides in single particle or quasi-single particle form of the present invention have a small number of sub-components (i.e., grain junctions) constituting the particles, so there is almost no change in primary particles caused by their volume expansion and contraction during charging and discharging, and thus the occurrence of cracks inside the particles is also significantly reduced. However, the lithium nickel-based transition metal oxides in single particle and / or quasi-single particle form require a high-temperature firing process, which may also affect the formation of the crystal structure (layer), resulting in a reduction in electrochemical performance. When the particle size is increased to reduce the generation of fine particles and the specific surface area of the powder, the above problems may become very serious.

[0033] Therefore, two kinds of particles with different median particle sizes can be mixed and used. In this case, during the rolling process, the small particles are mainly placed between the large particles and act as buffers, thereby minimizing the porosity and thus increasing the rolling density. However, in this case, the small particles acting as buffers are subject to large linear pressure, so the possibility of cracks appearing in the particles is very high. The particle sizes of the large particles and the small particles and their respective particle size distributions may be the main factors determining the arrangement structure between the particles, which may lead to different effects, such as damage to the particles themselves or the generation of fine particles away from the particles.

[0034] In other words, to achieve a high-density electrode, it is important to determine the characteristics of the particles used as the active material, such as their shape, size, and distribution. Therefore, the present inventors propose that by mixing large-particle-size lithium nickel-based transition metal oxides in the form of secondary particles and small-particle-size lithium nickel-based transition metal oxides in single particle and / or quasi-single particle form, the particle characteristics can solve the above problems and utilize the advantages of the two kinds of particles.

[0035] According to an embodiment of the present invention, the volume cumulative particle size distribution diagram obtained from the particle size distribution (PSD) of the positive electrode active material has a peak P on the small particle size side S and a peak P on the large particle size side L , and the B value obtained by the following Equation 1 is 4.0 to 17.0:

[0036] [Equation 1]

[0037] B = (D max - D L ) / (D S - D min )

[0038] Wherein, D max is the maximum particle size of the positive electrode active material, D minis the minimum particle size of the positive electrode active material, D L is the median particle size of peak P L , and D S is the median particle size of peak P S .

[0039] The volume cumulative particle size distribution graph can be measured using a laser diffraction method. For example, the volume cumulative particle size distribution graph can be obtained by dispersing lithium nickel-based transition metal oxide powder in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device, and irradiating ultrasonic waves of about 28 kHz with an output of 60 W. Through this graph, various data adopted in the present invention can be obtained.

[0040] B indicates the shape of peak P S and peak P L appearing in the particle size distribution graph, that is, the ratio of the peak widths, and can be measured slightly differently from the full width at half maximum (FWHM) commonly referred to as the peak width. For example, the full width at half maximum refers to the peak width at the half position of the maximum peak intensity, while the peak shape of the present invention is to determine the degree of difference between the minimum particle size, the maximum particle size, and the central particle size. Even if the full width at half maximum is the same, the difference between the minimum particle size, the maximum particle size, and the central particle size may be very different. That is, when the ratio of the widths of the two peaks satisfies the above range, a lithium secondary battery with improved performance can be obtained by increasing the energy density and suppressing cracks in the active material particles.

[0041] If the B value is less than 4.0, the roll density decreases, the degree of particle breakage during rolling increases, and the gas generated due to side reactions with the electrolyte increases, which may reduce the lifespan and increase the resistance. In addition, when the B value is greater than 17.0, the roll density decreases, and the breakage of large-diameter particles increases, which may lead to a reduction in performance such as energy density. Therefore, the B value can preferably be 5.0 or more, 5.5 or more, 6.0 or more, 6.5 or more, or 6.8 or more, 16.0 or less, 15.5 or less, 14.0 or less, 13.0 or less, 11.0 or less, or 10.0 or less.

[0042] According to one embodiment of the present invention, D 50 of the positive electrode active material can be 7 μm to 17 μm. D 50 is the average particle size of 50% of the volume cumulative of the mixed positive electrode active material mixed with large-diameter lithium transition metal oxide and small-diameter lithium transition metal oxide, and can be 8 μm or more, 9 μm or more, or 10 μm or more, 16 μm or less, 15 μm or less, or 14 μm or less. The above range of D 50 is the range where the optimal point between the cracking rate and the roll density can be found. It is ideal to control other particle size characteristics at a level where D 50 is within the above range.

[0043] In addition, the positive electrode active material may have a D of 56 μm or less max and a D of 0.1 μm or more min . D max is the particle size of the particle having the largest particle size among all the particles, and when particles larger than 56 μm are included, it may adversely affect the electrode process and energy density. D min is the particle size of the particle having the smallest particle size among all the particles, and when it is less than 0.1 μm, the proportion of particles less than 1 μm increases, so side reactions may become more serious due to the increased amount of fine powder generated. Therefore, since the content of the conductive material and the binder must be increased when configuring the electrode mixture, the energy density may decrease. Therefore, it is necessary to control the particle size so that particles smaller than the above diameter are not generated. That is, preferably, D max may be 53 μm or less, 50 μm or less, 47 μm or less, 43 μm or less, or 41 μm or less, and D min may be 0.3 μm or more, 0.5 μm or more, 0.55 μm or more, 0.6 μm or more, or 0.7 μm or more.

[0044] According to an embodiment of the present invention, the positive electrode active material may have a D of 5 μm to 20 μm L and a D of 1 μm to 10 μm S . Preferably, D L may be 7 μm or more, 9 μm or more, 11 μm or more, 13 μm or more, or 14 μm or more, 19 μm or less, 18 μm or less, or 17 μm or less. Preferably, D S may be 1.5 μm or more, 2 μm or more, 2.3 μm or more, or 2.4 μm or more, 9 μm or less, 7 μm or less, or 5 μm or less. The D 50 of the large particle size lithium nickel-based transition metal oxide may be similar to D L , and D S of the small particle size lithium nickel-based transition metal oxide may be similar to D 50 , but due to the difference in the peak width of the particle size distribution of each particle, they may not be substantially the same. D L and D S are ranges set to adapt to functions according to the roles that the large particle size and the small particle size must play respectively, and may be conditions required to achieve the effects of improving the roll pressing density and reducing the cracking rate.

[0045] In addition, according to an embodiment of the present invention, D L and D SThe difference can be from 6 μm to 15 μm. If the difference between the two particle sizes is less than 6 μm, the energy density cannot be improved due to the reduced effect of the bimodal property, and the capacity property may deteriorate due to the low roll pressing density itself. Additionally, when the difference is greater than 15 μm, performance deterioration is expected due to particle breakage of the particles in the small particle size distribution. Therefore, it is desirable to control the difference between the two particle sizes within the above range, preferably 7 μm or more, or 8 μm or more, 14 μm or less, or 13 μm or less.

[0046] According to an embodiment of the present invention, in the volume cumulative particle size distribution diagram obtained from the particle size distribution (PSD) of the positive electrode active material, peak P S has a maximum value I S and the ratio (I L / I L ) of the maximum value I S of peak P L ) can be from 0.2 to 1.5. This maximum value ratio refers to the ratio of the maximum heights of the two peaks, and can refer to the ratio between the particles of the particle sizes that occupy the largest volume in the large particle size particles and the small particle size particles respectively. If the particles with the largest volume particle size in the small particle size particles occupy more volume than the particles with the largest volume particle size in the large particle size particles, the roll pressing density and the cracking rate may deteriorate simultaneously, resulting in poor performance. Therefore, it is desirable to carefully control the particle size characteristics. Preferably, it can be 0.25 or more, 0.30 or more, 0.35 or more, or 0.40 or more, 1.30 or less, 1.20 or less, 1.10 or less, 1.00 or less, 0.90 or less, 0.80 or less, 0.75 or less, 0.70 or less, or 0.66 or less. If it is at least 1.00 or less, it can more effectively help improve the roll pressing density, high temperature life characteristics, and resistance characteristics.

[0047] In addition, the ratio A S of the integral area A S of peak P L to the integral area A L of peak P S / A L can be from 0.4 to 1.0. If the ratio of the maximum values refers to the volume ratio of the particles with the largest volume particle size, the ratio of the integral areas can refer to the total volume ratio. When the ratio of the integral areas is from 0.4 to 1.0, as described above, the effect of improving the roll pressing density while reducing the cracking rate can be expected. Preferably, the ratio of the integral areas can be 0.45 or more, 0.50 or more, or 0.55 or more, and can be 0.95 or less, 0.90 or less, 0.85 or less, or 0.80 or less.

[0048] According to one embodiment of the present invention, the mixing weight ratio of the small particle size lithium nickel-based transition metal oxide and the large particle size lithium nickel-based transition metal oxide can be from 90:10 to 20:80. Preferably, it can be 80:20 or less, 70:30 or less, or 60:40 or less, and can be 30:70 or more, or 40:60 or more. If the above mixing ratio range is satisfied, the roll pressing density can be maximized by optimizing the filling, and the particle breakage can be reduced by reducing the linear pressure during the roll pressing process.

[0049] Meanwhile, the positive electrode active material of the present invention may include a lithium nickel-based transition metal oxide. Specifically, a lithium nickel-based transition metal oxide having a composition represented by Chemical Formula 1 below:

[0050] [Chemical Formula 1]

[0051] Li 1+x Ni a Co b M 1 c M 2 d O 2-e X e

[0052] Wherein, M 1 includes one or more selected from Mn and Al; M 2 includes one or more selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb; X includes one or more selected from the group consisting of N, P, S, F, and Cl; 0 ≤ x ≤ 0.5, 0.5 ≤ a < 1, 0 < b ≤ 0.4, 0 < c ≤ 0.4, 0 ≤ d ≤ 0.05, and 0 ≤ e ≤ 0.05.

[0053] In the above Formula 1, M 1 is Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al; M 2 can be at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and is preferably at least one selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof. The M 2 element is not necessarily included, but when included in an appropriate amount, it can play a role in promoting grain growth or improving the crystal structure stability during calcination. In addition, X is an anion substituting for the oxygen site and can include N, P, S, F, or Cl.

[0054] 1 + x represents the molar ratio of lithium in the lithium nickel-based transition metal oxide, and can be 0 ≤ x ≤ 0.30, 0 ≤ x ≤ 0.20, or 0 ≤ x ≤ 0.15.

[0055] a represents the molar ratio of nickel among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0.60 ≤ a < 1.00, 0.70 ≤ a < 1.00, 0.75 ≤ a ≤ 0.99, 0.80 ≤ a ≤ 0.99, 0.82 ≤ a ≤ 0.99, 0.84 ≤ a ≤ 0.99, or 0.86 ≤ a ≤ 0.99.

[0056] b represents the molar ratio of cobalt among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0 < b < 0.30, 0.01 ≤ b < 0.25, 0.01 ≤ b < 0.20, or 0.01 ≤ b ≤ 0.15.

[0057] c represents M among all metals other than lithium in the lithium nickel-based transition metal oxide 1 and its molar ratio can be 0 < c < 0.30, 0.01 ≤ c < 0.25, 0.01 ≤ c < 0.20, or 0.01 ≤ c ≤ 0.15.

[0058] d represents the molar ratio of the M 2 element among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0 ≤ d ≤ 0.05, 0 ≤ d ≤ 0.03, or 0 ≤ d ≤ 0.02.

[0059] e represents the molar ratio of element X among all non-metals other than oxygen in the lithium nickel-based transition metal oxide, and can be 0 ≤ e ≤ 0.05, 0 ≤ e ≤ 0.02, or 0 ≤ e ≤ 0.01.

[0060] Meanwhile, the lithium nickel-based transition metal oxide may further include a coating on the particle surface, and the coating contains one or more coating elements selected from Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, and S.

[0061] When the coating is present on the surface of the lithium nickel-based transition metal oxide particles, the contact between the electrolyte and the lithium nickel-based transition metal oxide can be inhibited by the coating, thereby having the effect of reducing the transition metal elution or gas generation caused by the side reaction with the electrolyte.

[0062] Preferably, the coating may include Co as a coating element. When a coating containing Co is formed on the surface of the lithium nickel-based transition metal oxide particles in the form of single particles and / or quasi-single particles, the effects of improving the output and inhibiting the side reaction with the electrolyte can be obtained.

[0063] Method for manufacturing a positive electrode active material

[0064] Next, a method for manufacturing the positive electrode active material powder of the present invention will be described.

[0065] The method for manufacturing the positive electrode active material powder of the present invention includes the following steps: (S1) adding a transition metal-containing solution containing cations of nickel (Ni), cobalt (Co), and M 1 , an alkaline aqueous solution, and an ammonium solution and performing a coprecipitation reaction to prepare a positive electrode active material precursor; and (S2) mixing the positive electrode active material precursor and a lithium raw material and performing heat treatment thereon to prepare the positive electrode active material powder.

[0066] Through the conditions of the coprecipitation reaction and the firing conditions (such as the firing temperature and time of the lithium raw material and the precursor), the manufactured positive electrode active material can be in the form of single particles (formed by one grain segment), or in the form of quasi-single particles (a composite of 30 or fewer grain segments), or in the form of secondary particles (an aggregate of primary particles). The positive electrode active material of the present invention can be obtained by separately preparing a large particle size lithium nickel-based transition metal oxide and a small particle size lithium nickel-based transition metal oxide and then mixing them.

[0067] Hereinafter, each step of the method for manufacturing the positive electrode active material powder will be described in detail.

[0068] First, a transition metal-containing solution containing cations of nickel (Ni), cobalt (Co), and M 1 is prepared. For example, the transition metal-containing solution may include a nickel-containing raw material, a cobalt-containing raw material, and an M 1 raw material, where the M 1 raw material may be a manganese-containing raw material and / or an aluminum-containing raw material.

[0069] Thereafter, a positive electrode active material precursor can be prepared by adding a complexing agent containing an ammonium cation and an alkaline aqueous solution to the transition metal solution and performing a coprecipitation reaction.

[0070] The nickel-containing raw material may be, for example, nickel acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, etc., especially Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, nickel fatty acid, nickel halide, or a combination thereof, but not limited thereto.

[0071] The cobalt-containing raw material may be cobalt acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, etc., especially Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof, but not limited thereto.

[0072] The manganese-containing raw material can be, for example, a manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically manganese oxides such as Mn2O3, MnO2, Mn3O4, etc.; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate salts, manganese citrate, manganese fatty acid salts; manganese oxyhydroxide, manganese chloride, or a combination thereof, but not limited thereto.

[0073] The aluminum-containing raw material can be, for example, Al2O3, Al(OH)3, Al(NO3)3, Al2(SO4)3, (HO)2AlCH3CO2, HOAl(CH3CO2)2, Al(CH3CO2)3, aluminum halide, or a combination thereof.

[0074] The transition metal-containing solution can be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and an M 1 raw material to a solvent, where the solvent is particularly water, or a mixed solvent of water and an organic solvent that can be uniformly mixed with water (such as alcohol, etc.), or can be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and an M 1 raw material.

[0075] The complexing agent containing an ammonium cation can be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof, but not limited thereto. At the same time, the complexing agent containing an ammonium cation can be used in the form of an aqueous solution, where the solvent can be water, or a mixture of water and an organic solvent that is uniformly miscible with water (specifically, alcohol, etc.).

[0076] The basic compound can be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, its hydrate, or a combination thereof. The basic compound can also be used in the form of an aqueous solution, where the solvent can be water, or a mixture of water and an organic solvent that is uniformly miscible with water (specifically, alcohol, etc.).

[0077] A basic compound is added to adjust the pH of the reaction solution, and the addition amount can be such that the pH of the metal solution is 8 to 12.

[0078] The coprecipitation reaction can be carried out at a temperature of 35 °C to 80 °C under an inert atmosphere (such as nitrogen or argon).

[0079] Thus, a precursor of a cathode active material containing nickel, cobalt, and M 1 cations can be prepared.

[0080] By the above method, nickel-cobalt-M 1Hydroxide cathode active material precursor particles are precipitated in a reaction solution. By controlling the concentrations of the nickel-containing raw material, cobalt-containing raw material, and M-containing 1 raw material, a cathode active material precursor can be prepared such that the nickel (Ni) content in the total metal content is 70 mol% or more, 75 mol% or more, preferably 80 mol% or more, more preferably 82 mol% or more. The precipitated cathode active material precursor particles can be separated and dried according to a conventional method to produce a cathode active material precursor.

[0081] Thereafter, the cathode active material precursor and a lithium raw material are mixed and heat-treated.

[0082] The lithium raw material can be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or hydroxyoxide, without particular limitation as long as it is water-soluble. Specifically, the lithium raw material can be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more thereof can be used.

[0083] The cathode active material precursor and the lithium raw material can be mixed at a molar ratio of 1:1 to 1:1.30. The cathode active material precursor and the lithium raw material can be mixed, for example, at a molar ratio of about 1:1, about 1:1.05, about 1:1.07, about 1:1.10, about 1:1.5, about 1:1.20, or about 1:1.30, but is not limited thereto.

[0084] In the case of a high-Ni type NCM-based lithium composite transition metal oxide with a nickel (Ni) content of 70 mol% or more, the heat treatment can be carried out at a temperature of 650 °C to 1000 °C. The heat treatment can preferably be carried out, for example, at a temperature of 700 °C to 900 °C, and more preferably at a temperature of 720 °C to 870 °C. The formation of the cathode active material powder in the form of single particles and / or quasi-single particles is affected by the heat treatment temperature conditions.

[0085] Therefore, the manufactured cathode active material can have reduced particle breakage and crystal structure strain during the rolling process or during the charge and discharge process of a lithium secondary battery including the same, and can have improved initial resistance characteristics.

[0086] The heat treatment can be carried out in an air or oxygen atmosphere for, for example, 4 to 12 hours. Specifically, the heat treatment can be carried out, for example, for 4 hours or more, 6 hours or more, 8 hours or more, 10 hours or more, and can be carried out for 12 hours or less, 10 hours or less, 8 hours or less, and 6 hours or less.

[0087] Meanwhile, when preparing a lithium nickel-based transition metal oxide containing M 2 metal, or when preparing a lithium nickel-based transition metal oxide containing a non-metal (such as X) for anion substitution at the oxygen site, a raw material containing M 2 metal and / or a raw material containing an X element can be additionally mixed during the coprecipitation reaction or in the firing step. In this case, the raw material containing M 2 metal can be an acetate, carbonate, nitrate, sulfate, halide, sulfide or oxide of M 2 metal, and the raw material containing an X element can be a lithium salt of X or an acid containing X.

[0088] On the other hand, when a coating needs to be formed on the surface of the lithium nickel-based transition metal oxide, after the above heat treatment, the following steps can be further carried out: mixing the lithium nickel-based transition metal oxide prepared by the heat treatment with a coating raw material, and then heat-treating them. In this case, the mixing can be completed by solid-phase mixing or liquid-phase mixing, and the heat treatment can be carried out at an appropriate temperature according to the coating raw material. For example, the heat treatment of the coating process can be carried out at a temperature of 200 °C to 700 °C or 300 °C to 600 °C, but is not limited thereto.

[0089] In addition, when manufacturing the positive electrode active material powder of the present invention, it is preferably not to perform a water washing treatment after the heat treatment. Conventionally, when manufacturing a high-nickel (Ni)-type NCM-based lithium composite transition metal oxide, a water washing process is usually carried out after the heat treatment to reduce the content of lithium by-products. However, according to the research of the present inventors, it has been found that when the water washing process is carried out in the production of lithium nickel-based transition metal oxides in the form of single particles and / or quasi-single particles, the surface properties of the lithium nickel-based transition metal oxides deteriorate during the water washing, so the resistance increases. Therefore, when manufacturing the positive electrode active material powder of the present invention, it is preferably not to perform water washing, but to consume the remaining lithium on the surface of the lithium nickel-based transition metal oxide through a coating formation process. In this way, when manufacturing the positive electrode active material without washing the lithium nickel-based transition metal oxide, an increase in resistance caused by surface defects can be suppressed.

[0090] Positive electrode

[0091] The positive electrode of the present invention contains the positive electrode active material powder of the present invention as described above. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material powder of the present invention. Since the positive electrode active material powder has been described above, its detailed description will be omitted, and only the remaining components will be described in detail below.

[0092] The positive electrode current collector may include a highly conductive metal and is not particularly limited as long as the positive electrode active material layer can easily adhere thereto and is not reactive within the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. Moreover, the positive electrode current collector generally may have a thickness of 3 μm to 500 μm, and microscopic irregularities may be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector may be used, for example, in various shapes such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabrics.

[0093] If necessary, the positive electrode active material layer may optionally include a conductive material and a binder in addition to the positive electrode active material powder.

[0094] In this case, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material powder may be 80% by weight to 99% by weight, more specifically 85% by weight to 98.5% by weight, and excellent capacity characteristics can be exhibited when included within the above content range.

[0095] The conductive material is used to provide conductivity to the electrode, and any conductive material can be used without particular limitation as long as it has electron conductivity and does not cause chemical changes in the battery. Specific examples of the conductive material may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive tubes, such as carbon nanotubes; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more of them can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive material may be 0.1% by weight to 15% by weight.

[0096] Binders are used to enhance the adhesion between positive electrode active material particles and between the positive electrode active material and the current collector. Specific examples of binders may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene copolymer (PVDF - co - HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene - propylene - diene polymer (EPDM), sulfonated EPDM, styrene - butadiene rubber (SBR), fluororubber, polyacrylic acid, these polymers in which hydrogen is replaced by Li, Na or Ca, or various copolymers thereof, and a mixture of one or more of them may be used. Based on the total weight of the positive electrode active material layer, the content of the binder may be from 0.1 wt% to 15 wt%.

[0097] In addition to using the above - mentioned positive electrode active material powder, a positive electrode can be prepared according to a conventional positive electrode preparation method. Specifically, the above - mentioned positive electrode active material powder, and optionally a binder, a conductive material, and a dispersant can be dissolved or dispersed in a solvent to prepare a positive electrode slurry composition. The slurry composition can be coated on a positive electrode current collector and then dried and roll - pressed to prepare a positive electrode.

[0098] The solvent can be any solvent commonly used in the art. For example, any one or a mixture of two or more of dimethyl sulfoxide (DMSO), isopropyl alcohol, N - methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, or water can be used. The amount of the solvent can be sufficient to dissolve or disperse the positive electrode active material, the conductive material, the binder, and the dispersant (considering the coating thickness of the slurry and the manufacturing yield), and the viscosity of the slurry is allowed to be such that excellent thickness uniformity can be exhibited during the subsequent coating process for preparing the positive electrode.

[0099] Alternatively, a positive electrode can be prepared by the following process: casting the positive electrode slurry composition on a separate support, and then laminating the film peeled off from the support on the positive electrode current collector.

[0100] Electrochemical device

[0101] Next, the electrochemical device of the present invention will be described. The electrochemical device of the present invention includes the positive electrode of the present invention described above. Specifically, the electrochemical device can be a battery, a capacitor, etc., and more specifically, it can be a lithium secondary battery.

[0102] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separator and an electrolyte disposed between the positive electrode and the negative electrode. Since the positive electrode is the same as the above, its detailed description is omitted, and only the remaining components will be described in detail below.

[0103] In addition, the lithium secondary battery may optionally include a battery container that houses an electrode assembly formed of a positive electrode, a negative electrode, and a separator, and a sealing member that seals the battery container.

[0104] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector.

[0105] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, or silver, or an aluminum-cadmium alloy can be used. In addition, the negative electrode current collector generally may have a thickness of 3 μm to 500 μm, and, similar to the positive electrode current collector, microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes, such as a film, sheet, foil, net, porous body, foam, and non-woven fabric, etc.

[0106] In addition to the negative electrode active material, the negative electrode active material layer may optionally include a binder and a conductive material.

[0107] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples thereof can be: carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal substances capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiO β (0 < β < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites containing the metal substances and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more thereof can be used. In addition, a thin film of metallic lithium can be used as the negative electrode active material. Furthermore, low-crystalline carbon and high-crystalline carbon, etc. can be used as carbonaceous materials. Common examples of low-crystalline carbon can be soft carbon and hard carbon, and common examples of high-crystalline carbon can be irregular, planar, flaky, spherical, or fibrous natural graphite or artificial graphite, floating (Kish) graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.

[0108] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 80% by weight to 99% by weight.

[0109] The binder is a component that helps to bond the conductive material, the active material, and the current collector. Among them, based on the total weight of the negative electrode active material layer, the addition amount of the binder is usually 0.1% by weight to 10% by weight. Examples of the binder include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof, etc.

[0110] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Among them, based on the total weight of the negative electrode active material layer, the addition amount of the conductive material can be 10% by weight or less, preferably 5% by weight or less. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, it can be: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking carbon black; conductive fibers, such as carbon fibers and metal fibers; carbon fluoride; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive materials such as polyphenylene derivatives.

[0111] The negative electrode active material layer can be prepared by the following process: dissolving or dispersing the negative electrode active material and optionally the binder and the conductive material in a solvent to form a negative electrode slurry composition, coating the slurry composition on the negative electrode current collector, and drying. Alternatively, the negative electrode active material layer can be prepared by the following process: casting the negative electrode slurry composition on a separate support, and then laminating the film peeled from the support on the negative electrode current collector.

[0112] Meanwhile, in a lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a moving path for lithium ions. Any separator can be used without particular limitation as long as it is generally used as a separator in a lithium secondary battery. In particular, it is preferable to use a separator having excellent moisture retention ability for the electrolyte and low resistance to the transport of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer), or a laminated structure having two or more layers of the above polymers can be used. Moreover, common porous non-woven fabrics can be used, for example, non-woven fabrics formed of high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure can be selectively used.

[0113] In addition, the electrolyte for the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.

[0114] Specifically, the electrolyte may contain an organic solvent and a lithium salt.

[0115] Any solvent can be used as the organic solvent without particular limitation as long as it can be used as a medium that allows ions participating in the electrochemical reaction of the battery to move therethrough. Specifically, the organic solvent may be: an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene and fluorobenzene; or a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); an alcohol solvent such as ethanol and isopropyl alcohol; a nitrile such as R-CN (where R is a linear, branched, or cyclic C2 to C20 hydrocarbon group and may include a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among these solvents, carbonate solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant and a low-viscosity chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) that can improve the charge / discharge performance of the battery is more preferably used.

[0116] The lithium salt can be any compound without particular limitation as long as it can provide lithium ions used in the lithium secondary battery. Specifically, the anion of the lithium salt may be selected from F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2- , SCN - and (CF3CF2SO2)2N - At least one of the group consisting of, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. The lithium salt is preferably used at a concentration of 0.1 to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, whereby excellent electrolyte performance can be exhibited and lithium ions can move effectively.

[0117] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above electrolyte components, the electrolyte may further contain at least one additive, for example, halogenated alkylene carbonate compounds (such as ethylene difluorocarbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, based on the total weight of the electrolyte, the content of the additive may be 0.1 wt% to 5 wt%.

[0118] Examples

[0119] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments described herein.

[0120] Example 1

[0121] Mix the cathode active material precursor Ni 0.90 Co 0.05 Mn 0.05 (OH)2 and LiOH in a molar ratio of (Ni + Co + Mn):Li = 1:1.05, and then calcine and dry to prepare a large particle size lithium nickel-based transition metal oxide having the particle size characteristics shown in Table 1 below.

[0122] Mix the cathode active material precursor Ni 0.88 Co 0.06 Mn 0.06(OH)2 and LiOH are mixed in a molar ratio of (Ni + Co + Mn):Li = 1:1.05, and then calcined and dried to prepare small-sized lithium nickel-based transition metal oxides with particle size characteristics shown in Table 1 below.

[0123] The prepared large-sized lithium nickel-based transition metal oxides and small-sized lithium nickel-based transition metal oxides are mixed in a weight ratio of 60:40.

[0124] Examples 2 to 5 and Comparative Examples 1 to 2

[0125] Prepare large-sized and small-sized lithium nickel-based transition metal oxides with particle size characteristics shown in Table 1 below, and mix them in a weight ratio of 60:40.

[0126] Experimental Example 1: Confirmation of particle size characteristics of the positive electrode active material

[0127] The particle size characteristics of each mixed positive electrode active material prepared in the above Examples and Comparative Examples are confirmed by the following method.

[0128] Disperse 0.005 g of the mixed positive electrode active material in H2O as the dispersion medium, then introduce it into a laser diffraction particle size measuring device (Malvern MASTERSIZER 3000), and irradiate it with ultrasonic waves at about 28 kHz with an output of 60 W to obtain the volume-based particle size distribution diagram of each positive electrode active material. Obtain D L 、D S 、D 50 、D max 、D min 、I L 、I S 、A L and A S , and calculate the B value using Equation 1 below to obtain the data shown in Table 1 below.

[0129] [Equation 1]

[0130] B = (D max - D L ) / (D S - D min )

[0131] where D max is the maximum particle size of the positive electrode active material, D min is the minimum particle size of the positive electrode active material, D L is the median particle size of peak P L , and D S is the median particle size of peak P S .

[0132] [Table 1]

[0133] <![CDATA[D min > <![CDATA[D S > <![CDATA[D L > <![CDATA[D max > <![CDATA[D 50 > <![CDATA[I S / I L > <![CDATA[D L -D S > <![CDATA[A S / A L > B Example 1 0.76 2.70 14.1 27.4 12.5 0.69 11.4 0.57 6.9 Example 2 1.13 3.90 15.2 31.1 13.1 0.62 11.3 0.55 5.7 Example 3 0.59 2.40 14.1 31.1 11.1 0.78 11.7 0.66 9.4 Example 4 0.76 2.70 15.2 40.1 13.5 0.59 12.5 0.59 12.8 Example 5 0.76 2.70 16.2 45.6 13.8 0.61 13.5 0.55 15.2 Comparative Example 1 0.50 4.20 13.7 27.4 8.5 1.25 9.5 0.89 3.7 Comparative Example 2 0.76 2.70 10.5 45.6 7.5 1.21 7.8 0.84 18.3

[0134] Experimental Example 2: Rolled Density of the Positive Electrode Active Material

[0135] The rolled density (g / cm 3 ) and the amount of fine powder generated (volume %) of each positive electrode active material prepared in the examples and comparative examples were measured using a densitometer (Caver Pellet Press). Specifically, 3 g of each positive electrode active material prepared in the above examples and comparative examples was subdivided and tightly packed into a cylindrical metal mold with a diameter of 20 mm, and then a pressure of 9 tons was applied to obtain the rolled density (g / cm 3 ) from the weight and volume of the produced compact. After applying a pressure of 9 tons, the particle size distribution of the positive electrode active material was measured in the same manner as in Experimental Example 1, and the amount of fine powder less than 1 μm generated (volume %) was measured. The results are shown in Table 2 below.

[0136] [Table 2]

[0137] <![CDATA[Rolled density (g / cm 3 )]]> Amount of fine powder generated (volume%) Example 1 3.72 0.5 Example 2 3.68 0.45 Example 3 3.78 0.7 Example 4 3.77 0.4 Example 5 3.76 0.35 Comparative Example 1 3.55 5.5 Comparative Example 2 3.49 4.7

[0138] Referring to Table 2, it can be seen that the rolled density and the amount of fine powder generated in Examples 1-5 are superior to those in Comparative Examples 1 and 2.

[0139] Experimental Example 3: Evaluation of High-Temperature Storage Characteristics

[0140] Coin-type half-cells including each positive electrode active material of the examples and comparative examples were fabricated and then charged to 4.25 V. Then, two electrodes (loading amount: 400 mg) charged at a voltage of 4.25 V and a separator were placed at the bottom of the coin-type cell and fixed with washers. Thereafter, 15 μl of electrolyte (DEC REF.) was vacuum-injected twice, and each side was vacuum-sealed to a thickness of 1 cm using an aluminum bag with a size of 6.5×5 cm. Here, vacuum sealing means sealing under the single-cell vacuum sealing conditions of 95 kPa / 93 kPa. The coin-type half-cells fabricated as above were stored in a convection oven at 60 °C for 10 weeks, and then the amount of gas generated (volume change rate, %) was evaluated by comparing the change in cell volume. The results are shown in Table 3 below.

[0141] Experimental Example 4: Evaluation of High-Temperature Life and Resistance Characteristics

[0142] A single cell including a positive electrode and a negative electrode was fabricated. In the case of the positive electrode, each positive electrode active material powder prepared in the examples and comparative examples was applied to a current collector and dried to prepare the positive electrode. In the case of the negative electrode, natural graphite and artificial graphite were mixed at a ratio of 5:5 and used as the negative electrode active material, and a negative electrode was prepared using 95.6 wt% of the negative electrode active material, 0.9 wt% of a conductive material, and 3.4 wt% of a binder. The loading amount of the negative electrode was 10.7 mg / cm 2 , and the N / P ratio of the negative electrode and the positive electrode was fixed at 1.08.

[0143] At a temperature of 45 °C, 300 cycles were performed to measure the capacity retention rate (%) of the single cells containing each positive electrode active material of the examples and comparative examples, and the resistance increase rate was calculated by measuring the resistance after 300 cycles compared to the initial resistance. The results are shown in Table 3 below.

[0144] Capacity retention rate (%) = (Discharge capacity at the 300th cycle / Initial discharge capacity) × 100

[0145] Resistance increase rate (%) = (Resistance after 300 discharges / Initial resistance) × 100

[0146] [Table 3]

[0147]

[0148] Referring to Table 3, it can be seen that in the case of Examples 1 to 5 that satisfy the defined B value range (where the defined B value is used to control the shapes of the large-diameter particle peak and small-diameter particle peak in the mixed positive electrode active material mixed with large and small particles having a bimodal particle size characteristic), the high-temperature performance (i.e., the capacity retention rate and resistance increase rate at high temperature) is significantly superior to the comparative examples. In addition, in the case of the examples, as shown in Table 2, it was confirmed that although the roll pressing density was excellent, the amount of fine powder generated was small, reducing side reactions, and as a result, the volume change rate was also superior to the comparative examples.

Claims

1. A positive electrode active material, comprising: Large particle size lithium nickel-based transition metal oxide and small particle size lithium nickel-based transition metal oxide, Among them, The large particle size lithium nickel-based transition metal oxide is in the form of secondary particles, and the secondary particles are aggregates of primary particles, wherein the small particle size lithium nickel-based transition metal oxide is in the form of at least one of single particles and quasi-single particles, the single particle is formed by one grain segment, and the quasi-single particle is a composite of 30 or less grain segments, The volume cumulative particle size distribution diagram obtained from the particle size distribution (PSD) of the positive electrode active material includes a peak P on the small particle size side. S and the peak P on the large particle size side L , and the B value obtained by the following equation 1 is 4.0 to 17.0: [Equation 1] B = (D max - D L ) / (D S - D min ) Among them, D max is the maximum particle size of the positive electrode active material, D min is the minimum particle size of the positive electrode active material, D L is the median particle size of peak P L , and D S is the median particle size of peak P S .

2. The positive electrode active material according to claim 1, wherein, The positive electrode active material has a D of 7 μm to 17 μm 50 , a D of 56 μm or less max and a D of 0.1 μm or more min .

3. The positive electrode active material according to claim 1, wherein, The positive electrode active material has a D of 5 μm to 20 μm L and a D of 1 μm to 10 μm S .

4. The positive electrode active material according to claim 1, wherein The D of the positive electrode active material L and D S The difference is 6 μm to 15 μm.

5. The positive electrode active material according to claim 1, wherein, Peak P S The maximum value I S and Peak P L The maximum value I L The ratio I S / I L is from 0.2 to 1.

5.

6. The positive electrode active material according to claim 1, wherein, Peak P S The integrated area A S and the integrated area A L of peak P L The ratio A S / A L is from 0.4 to 1.

0.

7. The positive electrode active material according to claim 1, wherein, The weight ratio of the large particle size lithium nickel-based transition metal oxide to the small particle size lithium nickel-based transition metal oxide is 90:10 to 30:

70.

8. The positive electrode active material according to claim 1, wherein, The lithium nickel-based transition metal oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li 1+x Ni a Co b M 1 c M 2 d O 2-e X e wherein, M 1 comprises one or more selected from Mn and Al; M 2 comprises one or more selected from the group consisting of Ba, Ca, Mg, Sr, B, W, Zr, Y, Ti, V, Ta and Nb; X comprises one or more selected from the group consisting of N, P, S, F and Cl; 0 ≤ x ≤ 0.5, 0.5 ≤ a < 1, 0 < b ≤ 0.4, 0 < c ≤ 0.4, 0 ≤ d ≤ 0.05 and 0 ≤ e ≤ 0.

05.

9. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 8.

10. A lithium secondary battery comprising the positive electrode according to claim 9.

Citation Information

Cited By

  • Lithium ion secondary battery, positive electrode active material, preparation method and electric equipment

    CN119994146A